Efecto de la calendula (caléndula officinalis) para el tratamiento de gingivitis en caninos domésticos (canis lupus familiaris). - Cayo Papa, Wilma Alexandra (Ecuador: Latacunga: Universidad Técnica de Cotopaxi (UTC)., 2020)
The purpose of this research was to determine the effect of Calendula (Clendula Officinalis) for the treatment of Gingivitis in Domestic Canines (Canis LupusFamiliaris); for which 20 canines were used in the Citadel the mills neighborhood of Niagra of Canton Latacunga, the same ones that were subjected to the application of calendula: where to estimate the effectiveness were used treatments based on tincture and cream of the calendula. The results of the investigation, conclude that the effect of the calendula performed with the tincture applied twice a day for 30 days, showed the best behavior against the bacteria Echericha coli and Stapylococcus cuagulase negative with 0 CFU when counting the 30 days after application of the treatments, while in the treatments with tincture of marigold plus the cream applied every day and passing a day still bacteria were observed at 30 days post application. In relation to the blood count, the canines presented pictures of acute infection and stress at the beginning of the investigation, once the treatments were applied on day 30 of the investigation, some canines still presented alterations that may be caused by other factors outside the investigation. The results obtained indicate that 100% effectiveness of the calendula was observed in T2 when applied twice a day, passing 1 day during the 30 days of the evaluation. Results will allow the owner to know the degree of involvement of the bacteria in the canines creating awareness about the oral care of their pets. La presente investigación tuvo como finalidad determinar el efecto de la Caléndula (Caléndula Officinalis) para el tratamiento de Gingivitis en Caninos Domésticos (Canis LupusFamiliaris); para lo cual se utilizarón 20 caninos en la Ciudadela los molinos barrio del Niagra del Cantón Latacunga, los mismo que se sometieron a la aplicación de caléndula: donde para estimar la efectibilidad se emplearon tratamientos a base de tintura y crema de la caléndula. Los resultados obtenidos de la investigación, concluyen que el ...